Bridging the gap between cognitive tasks and abilities. - Percy, Tania L. M.; Matheson, Leonard N. (Work, 2025)
Background: This is the next entry in the WORK "Bridging the Gap" series. It continues the case study by describing procedures and methods used by occupational therapists in work-oriented neurorehabilitation to help clients bridge the gap between their work tasks and their abilities, using information from the Occupational Information Network (O*NET). Objective: To demonstrate the potential of integrating O*NET information with occupational therapy procedures and practices. Methods: A competitive employment disability case study provided the context for an interdisciplinary work-oriented reflective practice and dialogic inquiry approach to post-professional mentoring involving the authors and a fictional client's occupational therapist. The dialogue focuses on integrating information from O*NET about the target job's tasks and necessary abilities to improve client-centered practice for persons focused on returning to competitive employment. Results: In this case study, O*NET information facilitated return-to-work planning and the selection of evaluation and therapy tools. Information about the client's job tasks found in O*NET was used to set a detailed vocational ecological context for work-oriented services, beginning with the intake interview. Concerns about the use of self-report data were addressed. Screening for executive dysfunction with the BRIEF questionnaire guided clinical focus on O*NET cognitive ability variables. Conclusions: This case study shows how O*NET empirical data can improve the relevance of Occupational Therapy assessment and treatment for individuals aiming to return to competitive employment. The study illustrates how O*NET data can help guide occupational therapy intervention by addressing clients' specific concerns about potential limitations in their ability to perform job tasks.